Suitability Of Physical Oceanographic Conditions To Ministerial Decree No. 64/Kepmen-Kp/2020 On The Establishment Of Gili Ketapang Marine Protected Area - Rudi Siap Bintoro; Qomariyatus Sholihah; Marjono; Gatot Ciptadi; Ali Azhar (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
Marine conservation areas in small island environments require compatibility between management zoning and local physical oceanographic conditions to function effectively and sustainably. Gili Ketapang, located in the Madura Strait, has been designated as a Marine Conservation Area under the Decree of the Minister of Maritime Affairs and Fisheries No. 64/KEPMEN-KP/2020. However, evaluations of zoning suitability based on physical oceanographic characteristics remain limited. This study aims to assess the suitability of zoning within the Gili Ketapang Marine Conservation Area using key physical oceanographic parameters, including currents, waves, tides, and wind. Tidal analysis was conducted using the Admiralty method to determine tidal type and sea level characteristics. Wave and current data were obtained from Copernicus Marine Reanalysis with a 3-hour temporal resolution over a ten-year period, while wind data were used to support seasonal analysis. Zoning suitability was evaluated by comparing the analyzed oceanographic conditions with relevant criteria for coastal and marine utilization. The results indicate that the waters of Gili Ketapang are characterized by a mixed, mainly semidiurnal tidal regime, with a Formzahl value of 1.3. Seasonal variability in currents and wave conditions reveals periods that are less favorable for utilization activities in certain sub-zones, particularly within the Aquaculture Sub-Zone. These findings suggest that zoning suitability is dynamic and strongly influenced by seasonal oceanographic variability. This study highlights the importance of integrating long-term physical oceanographic analysis into the evaluation and management of marine conservation zoning, especially in small island environments with high hydrodynamic dynamics.